The relationship between negative symptom subdomains and cognition. Issue 10 (18th April 2016) - Lim, J.; Lee, S.-A.; Lam, M.; Rapisarda, A.; Kraus, M.; Keefe, R. S. E.; Lee, J.
Abstract : Background: Negative symptoms and cognitive deficits in schizophrenia are partially overlapping. However, the nature of the relationship between negative symptoms and cognition remains equivocal. Recent reviews have demonstrated the presence of two negative symptom subdomains, diminished emotional expression (DEE) and avolition. In view of this, we sought to clarify the relationship between negative symptoms and cognitive domains. Method: A total of 687 participants with schizophrenia were assessed on measures of psychopathology and cognition. Three cognitive factors, namely executive function, fluency/memory and speed/vigilance were computed from the cognitive tests. Confirmatory factor analysis was utilized to examine if a one-factor or two-factor negative model was applicable to our sample. Subsequently, the relationships between negative symptoms and cognition were examined using structural equation modeling. Results: Results demonstrated that the two-factor model fitted the data well. While negative symptoms were mildly to moderately associated with cognition, we found that DEE had unique associations with cognition compared to social avolition, contributing to the validity of the constructs and suggesting the possibility of common underlying substrates in negative symptoms and cognition. Conclusions: Our study highlighted the need to classify DEE and social avolition separately as both are necessary in refining the complex relationship between negative symptoms and cognition as well as potentially guiding treatment and management of schizophrenia.